Dental anthropological status of the human population found in the Roman site of Viminacium necropolis "Kod Koraba" - Mikić Ilija; Lisul Bogdan; Grga Đurica (Serbian Medical Society - Dental Section, Belgrade, 2019)
Introduction The "Kod Koraba" site is located in the territory of antique Viminacium. Archaeological excavations were carried out from 2005 to 2008. On this occasion, a necropolis with a total of 77 graves was explored, which according to archaeological contributions can be dated to the period from 2nd to 4th century AD (Roman period). The aim of this study was to provide, on the basis of the results of dental anthropological analysis of osteological material from the necropolis "Kod Koraba", data of the dental status and pathological changes of the oral cavity and teeth in human population that inhabited this area of antique Viminacium from 2nd to 4th century AD. Material and method During the archaeological excavations from 2005 to 2008, a total of 77 graves were explored. Of this number, due to lower degree of preservation, the dental status of 45 individuals was analyzed. Of these, 36 belonged to adult individuals and nine were children. Functional methodology used in previous studies of human populations of the prehistoric period was applied in order to compare obtained results with similar ones as well as with the status of the oral cavity and teeth of the current population. Results The obtained results supplemented the picture of dental health status of ancient populations in Viminacium. They indicated high degree of abrasion and dental plaque, the presence of caries within the expected limits for the studied period, as well as the presence of other dental pathologies such as periodontal disease and periapical processes present in the current human population. Conclusion Anatomo-morphological status of the teeth and the jaw of the human population from ancient Viminacium are similar with the characteristics of modern man. Pathological changes of the oro-facial system of modern man were present in the studied human population of Roman period, with different values of their distribution.